The Flora of Kurgans in the Desert Steppe Zone of Southern Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
Abstract: Results of the studies on biodiversity of the kurgan flora in the desert steppe of the Black Sea Lowland (the southern part of Kherson Region) are presented. Twenty-six of about 130 kurgans higher than 3 m, distributed over an area of approx. 1500 km2, were surveyed. The kurgan flora was estimated at 305 species; the number of species on particular kurgans ranged from 48 to 103, 82 on average. The species of particularly high floristic value were: Allium regelianum, Anacamptis picta (= Orchis picta), Cerastium ucrainicum, Dianthus lanceolatus, Linaria biebersteinii, Muscari neglectum, Senecio borysthenicus, Stipa capillata, and Tulipa schrenkii. The spectrum of life forms of the kurgans flora generally corresponded to the spectrum for the desert steppe zone (almost a half of the flora consisted of therophytes and short-living perennials). Species of alien origin constituted 23% of the kurgans flora, which does not indicate significant anthropogenic influence. Species with wide Mediterranean-Eurasian ranges predominated among anthropophytes. Only 9 species were the synanthropic newcomers, i.e. kenophytes. The phytosociological range of the kurgans flora was quite wide. Species of two classes, Festuco-Brometea and Stellarietea mediae were predominant, which also confirmed the semi-natural character of the kurgan flora. The kurgans constitute a distinctive element of the southern Ukraine landscape. The state of preservation of their plant cover varies. Floristic richness, a share of rare and protected species, as well as shares of non-synanthropic (steppe and halophilous) species can be assumed as the criteria for its assessment. The recommendations regarding kurgans that should be under protection, not only as archaeological sites but also as nature monuments, was based on these assessment criteria.
Keywords: kurgans` flora, barrows, refugia of steppe flora, floristic diversity, Pontic desert steppe, protection of kurgans, Kherson Region.